Legal and shariah issues in partnership law concerning Musharakah/Mudarabah venture capital practised by Islamic financial institutions in Malaysia - Md Dahlan, Nuarrual Hilal (2013)
lslamic banking has gained its foothold in Malaysia since the early 1980s. Ever since its establishment, various lslamic banking products have been introduced and practised in Malaysia.One of the products is lslamic partnership product of venture capital facility using Musharakah or Mudarabah. It is a trite practice that for lslamic banking product to be legal and shariah compliant, the product must fulfill the requirements of the shariah (Islamic law) and Malaysian law.Under the Malaysian law, Partnership Act 1961 (Act 135)('PA1) governs the creations and existence of all partnership undertakings.However, there is no corresponding statute which controls the creations of lslamic partnership products including the Musharakah/Mudarabah Venture Capital.Pursuant to the provisions under the Civil Law Act 1956 (Act 67)(Revised - 1972), unless there is a written law, the applicable law for states in Malaysia for the partnership undertaking is the law of England as that enforced in 1956 (for states in Malaya), 1951 (for Sabah) and 1949 (for Sarawak).As there is a written law on partnership viz the PA, then the PA, being the written law, will be the governing law.The issue is this: Does Musharakah/Mudarabah Venture Capital, being an Islamic partnership, likewise subject to the PA? There is nothing in the PA to indicate that Islamic Partnership falls under it.Nevertheless, the lslamic Financial Services Act 2013 (Act 759)('IFSA1) provides that all lslamic banking products must comply with Shariah (Islamic Law). Hence, Musharakah/Mudarabah Venture Capital must comply with the requirements of the Shariah to become a shariah compliant product.But, how if Musharakah/Mudarabah Venture Capital does not comply with the requirements of the PA? Will this not affect the validity of Musharakah/Mudarabah Venture Capital and thus it cannot be enforceable in the Malaysian court of law? This paper will highlight the intricacies and issues in the provisions of the existing PA with regard to the Musharakah/Mudarabah Venture Capital.The research methodology of this paper is a hybrid of shariah and legal research methods.The authors will also provide some suggestions in dealing with the intricacies and issues to warrant the validity of the Musharakah/Mudarabah Venture Capital, both in the law and shariah perspectives.